Targeted : [large type] three romantic suspense novellas - Eason, Lynette; Blackburn, Lynn Huggins; Walters, Natalie, 1978- (Thorndike Press large print Christian fiction series., 2023)
"In On the Run, Daria Nevsky must go on the run to find out who wants her dead - and Dr. Ryker Donahue refuses to let her do it alone. In Deadly Objective, when the vice president's son enters the crosshairs of a killer, some lines will have to be crossed to keep him safe. In Caught in the Crosshairs, there is no love lost between former Army PSYOPS officer Ari Blackman and CIA officer Claudia Gallegos after Claudia is implicated in the murder of a Saudi prince. But to prevent a coup that would put America at risk, they'll have to learn to trust each other before it's too late"--